G266 Improving knowledge and confidence in parents to care for their neonates using video education: an interventional study in a resource-limited setting. (May 2019) - Wilson, A; Arinitwe, R; Cartledge, P
Abstract : Aim: To investigate whether showing a short video on a specific topic could change the knowledge and confidence of carers in caring for a sick newborn. Methods: A prospective multi-center interventional study conducted from May-August 2018. Mothers of neonates on the postnatal or neonatal ward at a Rwandan urban district and teaching hospital were invited to participate. Of 65 identified women, 59 met inclusion criteria. Parents were shown 'How to increase breastmilk supply' a seven-minute video in the local language from https://globalhealthmedia.org/. The video was shown on a laptop computer. Participants completed a Likert based questionnaire before and after watching the video. Results: Of the 59 participants, only ten (16.9%) had previously received teaching on increasing breast milk supply. Likert scores were combined to form composite knowledge and confidence scores which statistically significant increased after watching the video (table 1 ). Satisfaction questions revealed that all participants (100%) reported 'I enjoyed watching the video' and could 'hear the voice clearly.' Only 2 (3.4%) felt the video was too long. Conclusion: In the resource-limited setting, neonatal mortality remains high, and the ratio of trained health professionals to patients is low. Parents are an underused resource for providing primary neonatal care but require some education to provide this safely. The results show a significant improvement in knowledge and confidence of the participants. There is scope for further research of video education, e.g., to assess if implementation results in improved care and outcomes. Based on these results we recommend incorporating video education into parental education. There are limitations: it was conducted in an urban setting, only women were assessed, and there may have been acquiescence bias.